ANALISIS PENGARUH ISLAMIC BRANDING TERHADAP KEPUTUSAN KONSUMEN UNTUK MEMBELI PRODUK - Elok Fitriya (Universitas Muhammadiyah Jember, 2017)
Abstract: This study aims to determine the influence of brand islamic to consumer decisions in buying goods. This research is a kuntitatif research. The population in this study were students in jember district. Samples of research students of Muhammadiyah University of Jember. The data collected in the form of primary data is questionnaire. Data processing techniques with tools SPSS 19. The results of the analysis states that the brand islamic effect on consumer decisions in making purchases.Keywords: Islamic Branding, Product, Purchase Decision